Empowering Rural-Remote Doctors Through Distance CME: a Literature Study - Kristian Wongso Giamto (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2016)
Background: Doctors in rural and remote areas in eastern Indonesia, particularly North Maluku (northern part of the Moluccas Islands), are burdened with difficulties in their daily practice due to shortage of radiology or laboratory devices and other medical specialties. Travel distance and cost sometimes made referral to a better health facility impossible. They also have limited accessibility to live Continuing Medical Education (CME), due to relatively high travel cost and limited health professionals remaining while they are absent. However, in this challenging situation, they still obliged to deliver the most optimal medical services possible. In some ways, such setting is more challenging than working as a doctor in urban area.Method: This paper derived its data from scientific journal publications, newspaper and also direct interview.Results: Online CME may be a very promising method to empower doctors in rural and remote settings. More awareness to the significance of CME, especially, to rural and remote doctors is needed. Further advocacy and collaboration among stakeholders are needed to support this idea, which is relevant not only to rural and remote doctors in North Maluku, but also in other eastern parts, and perhaps in other remote areas in entire Indonesia.Conclusion: Online CME, as proven by evidence-based findings, will reduce professional isolation and equip them cognitively. This empowerment will ultimately benefit patients and, indirectly, other sectors as well.